Efficient Heat Dissipation and Cyclic Electron Flow Confer Daily Air Exposure Tolerance in the Intertidal Seagrass Halophila beccarii Asch - Fang, Yang; Jiang, Zhijian; Zhao, Chunyu; Li, Linglan; Ranvilage, Chanaka Isuranga Premarathne Maha; Liu, Songlin; Wu, Yunchao; Huang, Xiaoping (Frontiers in Plant Science, 2020)
Seagrasses inhabiting the intertidal zone experience periodically repeated cycles of air exposure and rehydration. However, little is known about the photoprotective mechanisms in photosystem (PS)II and PSI, as well as changes in carbon utilization upon air exposure. The photoprotective processes upon air exposure in Halophila beccarii Asch., an endangered seagrass species, were examined using the Dual-PAM-100 and non-invasive micro-test technology. The results showed that air exposure enhanced non-photochemical quenching (NPQ) in both PSII and PSI, with a maximum increase in NPQ and Y(ND) (which represents the fraction of overall P700 that is oxidized in a given state) of 23 and 57%, respectively, resulting in intensive thermal energy dissipation of excess optical energy. Moreover, cyclic electron transport driven by PSI (CEF) was upregulated, reflected by a 50 and 22% increase in CEF and maximum electron transport rate in PSI to compensate for the abolished linear electron transport with significant decreases in pmfLEF (the proton motive force [pmf]) attributable solely to proton translocation by linear electron flow [LEF]). Additionally, H+ fluxes in mesophyll cells decreased steadily with increased air exposure time, exhibiting a maximum decrease of six-fold, indicating air exposure modified carbon utilization by decreasing the proton pump influxes. These findings indicate that efficient heat dissipation and CEF confer daily air exposure tolerance to the intertidal seagrass H. beccarii and provide new insights into the photoprotective mechanisms of intertidal seagrasses. This study also helps explain the extensive distribution of H. beccarii in intertidal zones.